Doris Lessing oltre il muro. Catastrofe e trascendenza in "Memorie di una sopravvissuta" - Tirino, Mario (Philosophy Kitchen - Rivista di filosofia contemporanea, 2019)
Memoirs of a survivor is one of Doris Lessing’s most complex and experimental novels. In this essay we analyze the evolution of the narrative model defined as “crisis and transcendence” (Kuns 1980). In particular, the writings of Doris Lessing enters into connection with Ferdinand Tönnies’ sociology of the community and Jacques Ellul’s philosophy of technology. From a sociocultural perspective, this paper tries to highlight the major value of this novel: Lessing manages to push the dystopian narration beyond its limits, to change the trajectory towards an etheropia (Foucault 1967), which passes through the radical challenge of Western epistemology and culture.